Social Capital as a Driver of Performance Among Generation Z Employees in Jakarta - Qatrunnada Qatrunnada; Didin Hikmah Perkasa (Journal of Social Commerce, 2026)
This study examines how occupational stress, workplace conflict, and organizational communication influence the work performance of Generation Z employees in Jakarta, Indonesia. The research is motivated by growing concerns over well-being and productivity among young professionals in urban settings, where high work demands and interpersonal challenges are prevalent. Using a quantitative approach, data were collected via surveys from 120 Gen Z employees across multiple industries in Jakarta. Multiple regression analysis was applied to assess both individual and collective impacts of the variables. Findings reveal that work-related stress negatively, though not significantly, impacts performance, whereas workplace conflict and organizational communication show positive and significant effects, with the latter emerging as the strongest predictor. Together, the three variables account for 26.5% of the variance in employee performance. These results underscore the value of fostering transparent communication and constructive conflict resolution to support the performance of young employees in today’s evolving workplace.